2016
DOI: 10.3892/mmr.2016.5750
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin-induced autophagy and apoptosis in a human prostate cancer cell line

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 61 publications
(60 reference statements)
1
40
0
Order By: Relevance
“…Diosgenin exerts its tumor suppressive function to induce apoptosis by down-regulating MALAT1/STAT3 signaling in gefitinib-resistant non-small cell lung cancer [30]. In addition, diosgenin activates tumor cell autophagy and apoptosis by inhibiting the phosphorylation of phosphoinositide 3-kinase, Akt, and the mammalian target of rapamycin, thereby decreasing signaling through this pathway [31]. Furthermore, diosgenin can improve intestinal microbiota, which may increase immune functions to enhance the therapeutic efficacy of the checkpoint protein, PD-1, when treating melanoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…Diosgenin exerts its tumor suppressive function to induce apoptosis by down-regulating MALAT1/STAT3 signaling in gefitinib-resistant non-small cell lung cancer [30]. In addition, diosgenin activates tumor cell autophagy and apoptosis by inhibiting the phosphorylation of phosphoinositide 3-kinase, Akt, and the mammalian target of rapamycin, thereby decreasing signaling through this pathway [31]. Furthermore, diosgenin can improve intestinal microbiota, which may increase immune functions to enhance the therapeutic efficacy of the checkpoint protein, PD-1, when treating melanoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the concentration responses of diosgenin‐induced cytotoxicity appear to vary among prostate cancer cell types. Previous studies have demonstrated that diosgenin between 30 and 240 μM caused cyotoxicity for 48 hours in DU145 human prostate cancer cells . The DU145 cell line was derived from a central nervous system metastasis, of primary prostate adenocarcinoma origin, removed during a parieto‐occipital craniotomy .…”
Section: Discussionmentioning
confidence: 99%
“…Though it is supposed that the main ingredients contained in Japanese yams are polysaccharides, proteins, and amino acids, which are responsible for its medicinal action, [ 3–6 ] there are not enough data in vivo. Diosgenin, which is a physiologically active substance found in yam species and extracts of yam, was investigated to assess its functionality, [ 7,8 ] but few studies have been performed that use whole Japanese yam in vivo. [ 9,10 ] The results of cultured cells indicated that diosgenin had the ability to cure hepatic fibrosis and inhibit the proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,10 ] The results of cultured cells indicated that diosgenin had the ability to cure hepatic fibrosis and inhibit the proliferation of cancer cells. [ 7,8 ] Chronic administration of Sanyaku inhibited an increase in body weight, but a single administration of diosgenin did not have an effect on body weight. [ 9 ] Kusano et al.…”
Section: Introductionmentioning
confidence: 99%